Surgical Ventricular Restoration for Post infarction Left Ventricular Aneurysm - JR Vijay Kumar; HS Natraj Setty; Rajiv Ananthakrishna; Rahul Patil; Seetharama PS Bhat; CN Manjunath (International Journal of Vascular Surgery and Medicine - Peertechz Publications, 2017)
Surgical ventricular restoration is a procedure designed to restore or remodel the left ventricle. Surgical ventricular restoration by means of the Dor procedure is a surgical option in patients with coronary artery disease, postinfarction left ventricular aneurysm (LV aneurysm) or ischemic dilated cardiomyopathy with or without ventricular tachycardia. Postinfarction left ventricular remodeling is characterized by LV dilatation and abnormal geometry leading to systolic and diastolic dysfunction. Development of a left ventricular aneurysm is a serious long-term complication of Acute Myocardial Infarction. We report a 69 year old male presented with haemodynamically significant ventricular tachycardia, successfully underwent DOR Procedure with complete recovery.